Perlindungan Hukum Bagi Pengguna Layanan Internet Banking Menurut Undang-Undang No. 8 Tahun 1999 Tentang Perlindungan Konsumen - Hidayah, Nur; B, Baidhowi; Novita, Yustina Dhian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of information technology has driven the transformation of banking services through internet banking which provides easy access and transaction efficiency for customers. However, this progress also increases the risks faced by customers, especially related to unclear agreements, unilateral changes in provisions, and the use of detrimental standard clauses. This study aims to analyze legal protection for users of internet banking services according to Law No. 8 of 1999 concerning Consumer Protection. The method used is empirical legal research with a positive law approach and field data collection. The results of the study indicate that although there are no specific regulations that explicitly regulate internet banking, legal protection for customers can still be implemented through the interpretation of the Consumer Protection Law and other related regulations. This law provides a strong legal basis to protect customer rights from unilateral practices and imbalances in credit agreements. However, the implementation of this legal protection still faces challenges, especially related to customer legal awareness and legal certainty. Therefore, strengthening regulations and legal education are needed to improve protection for users of internet banking services in Indonesia.